Modern Lifestyle Transformation: The Role of an Agile Android Diary App for Time Management and Self-Reflection - Andi Adbiyah Kurnia Dela; Nurhaliza Nurhaliza; Winda Winda (Journal of Digital Technology and Computer Science, 2024)
The rapid development of information technology drives the need for simple yet functional mobile applications to support daily productivity. One solution that is increasingly in demand is the short notes application, which allows users to record ideas, tasks, or important information quickly and practically. This study aims to design and develop an Android-based shortnotes application that prioritizes ease of use, efficiency, and local data storage without requiring an internet connection or integration with an external database. The system development method is carried out through several stages, namely planning, needs analysis, interface design, code implementation, and application testing. The Java programming language is used in the coding process with Android Studio as the main development environment. This application utilizes SharedPreferences and local file storage as data storage media, which are chosen to maintain the simplicity and efficiency of application performance on the user's device. The main features of the application include creating new notes, editing, deleting, and checking notes based on the results produced. The test results using the emulator show that the application runs smoothly and responsively in various usage scenarios. With a minimalist and intuitive interface, this application is expected to help users manage their daily notes more effectively.